Cigarette smoking and periodontal disease among 32-year-olds: a prospective study of a representative birth cohort - W. Murray Thomson (Blackwell Synergy, 2007)
Background: Smoking is recognized as the primary behavioural risk factor for periodontal attachment loss (AL), but confirmatory data from prospective cohort studies are scarce. Aim: To quantify the association between cigarette smoking patterns and AL by age 32. Methods: Periodontal examinations were conducted at ages 26 and 32 in a longstanding prospective study of a birth cohort born in Dunedin (New Zealand) in 1972/1973. Longitudinal categorization of smoking exposure was undertaken using data collected at ages 15, 18, 21, 26 and 32. Results: Complete data were available for 810 individuals of whom 48.9% had ever smoked (31.5% were current smokers). Compared with never-smokers, long-term smokers (and other age-32 smokers) had very high odds ratios (ORs of 7.1 and 5.7, respectively) for having 1 1sites with 5 1mm AL, and were more likely to be incident cases after age 26 (ORs of 5.2 and 3.2, respectively). Two-thirds of new cases after age 26 were attributable to smoking. There were no significant differences in periodontal health between never-smokers and those who had quit smoking after age 26. Conclusions: Current and long-term smoking in young adults is detrimental to periodontal health, but smoking cessation may be associated with a relatively rapid improvement in the periodontium.